"Reviving Kali Bein : Addressing the Re-Pollution Sources and and Exploring Solutions for Sustainable River Management" - Kiranjeet Jassal; Jasmine Kohli (International Journal of Environmental Planning and Development Architecture, 2023)
All aspects of the earth’s environmental system are impacted by human assault on the planet that includes vast conversion of land use, extraction of mineral resources, use and misuse of surface water and ground water which altered the natural flow of energy and resources within the environment. This paper reviews the present position of kali ben rivulet, which flows through the state of Punjab in India, has found to be polluted once again. In this study we assessed the current level of pollution in the river by conducting a survey of the river, which was causing a significant increase in pollution levels. Water sample were not collected in this study, but the visual evidence of domestic waste being discharged into the river is a cause for concern. The pollution of the Kali Bein Rivulet has implication for the local communities who rely on it for daily needs. The study recommends that immediate action is taken to stop the discharge of domestic waste into rivulet. This could achieved through the implementation of stricter regulations and penalties for polluters as well as education and awareness campaigns for local communities on the importance of protecting the river and its ecosystem.
Keywords: Kali Bein; Saint Seechwal; Sultanpur Lodhi; Untreated water; Wetlands